INTEGRITAS DIRI ANAK JALANAN DI LAMPU MERAH SIMPANG ARIFIN AHMAD PEKANBARU - Pratiwi, Hayati Nur; Rosmawati, Rosmawati; Donal, Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Research with the title self-integrity street children at Arifin Ahmad red cross intersection Pekanbaru City against the backround of the rise of street children found in several places in the city of Pekanbaru. Especially the Arifin Ahmad red light area. Street children have a bad image in the eyes of the community but still have good integrity to be accepted by the community. After conducting research in the Arifin Ahmad red light area of Pekanbaru city, the integrity of street children at the Arifin Ahmad red cross intersection in Pekanbaru city : Honesty, street children consider that honesty is very important. By having an honest nature, there will be many friends or other people who will believe. Then out of fear of being unreliable, they choose to rarely make promises to other people. According to them in other to complete the work on time, namely by directly doing it. Even the reason they are willing to work hard on the road, just because they want to help parents. Responsible, street children have a high level of responsibility, this can be seen when they apologize when making wrong decisions. If the borrowed item was damaged, they are willing to repair it or buy a new item.Key Words: street children, self-integrity.